Tree-ring δ2H records of lignin methoxy indicate spring temperature changes since 20th century in the Qinling Mountains, China - Lu, Qiangqiang; Liu, Xiaohong; Tan, Liangcheng; Keppler, Frank; Treydte, Kerstin; Wieland, Anna; Zhang, Lingnan; Shi, Xinwei; Zhang, Yu; Wang, Yabo; Zeng, Xiaomin; Liu, Jun; et al. (Dendrochronologia, 2022)
Stable hydrogen isotope ratios of wood lignin methoxy groups (δ2HLM values) of mid-latitude forests are increasingly applied to reconstruct δ2H patterns in precipitation of regional to sub-continental scales. To date, the knowledge about the effect of topographic factors on δ2HLM values is still scare, especially in the biogeographic boundary. We measured tree-ring δ2HLM chronologies (1901-2018) from two typical conifer species at three sites with different altitudes of a north-ridge-south transect of the Qinling Mountains (central China), where covers the climate transition zone from warm temperate to subtropics. The δ2HLM chronologies of the north and the south slopes were characterized by a decreasing trend between 1901 and 1955, which turned into a positive trend after 1955. In contrast, the mountain ridge site located at the highest altitude showed continuous increasing δ2HLM values over the entire period from 1901 to 2018. The highest correlations between temperature and δ2HLM chronologies were found for the northern slope and the mountain ridge region spring temperatures (March-May). The observed abrupt changes in the δ2HLM values since the 1950s at lower elevation sites might reveal slope-related moisture effects which superimpose local temperature patterns. During the rapidly warming period 1955-2018, the higher correlations of the δ2HLM chronologies with the spring and mean annual (previous November to current October) temperatures were detected on the warmer northern slope. In summary, although the variations of measured δ2HLM of the three investigated sites reflect geographic-specific hydrological characteristics, the low-frequency temperature changes are documented in the δ2HLM values.
In der chemischen Formel des Titels erscheint die Ziffer 2 hochgestellt
Gesehen am 07.02.2023